First assessment of factors affecting the breeding success of two stork species in lowland Nepal using Bayesian Network models - Sundar, K.S. Gopi; Koju, Roshila; Maharjan, Bijay; Marcot, Bruce G.; Kittur, Swati; Gosai, Kamal R. (Wildfowl, 2019)
Agricultural landscapes in south Asia have high human densities, experience year-round cropping, and the few remaining wetlands experience heavy human use. Factors affecting the breeding success of colonially-nesting waterbirds in such conditions are poorly understood. Using Bayesian Network (BN) models, we explored the importance of colony size, extent of persisting wetlands, human influence as proximity to habitation, and variation in landscape conditions due to changing crops (season) on the breeding success of two stork species – the Asian Openbill Anastomus oscitans and the Lesser Adjutant Leptoptilos javanicus– in lowland Nepal. Hypotheses were framed a priori to understand relative influences of each variable on breeding success, and to determine if heavily-used wetlands could ameliorate effects due to colony size and human presence. The model with all four covariates had best performance for both species, underscoring that complex combinations of factors affected stork breeding success in Nepal. In line with expectations, the importance of covariates differed between species. Proximity to human habitation and progression of season best explained breeding success for Asian Openbills, while season and the extent of wetlands around colonies best explained Lesser Adjutant breeding success. Wetland extent mediated some of the density-dependent effects, and also ameliorated effects linked to proximity to human habitation for both species, but had a weak ameliorating impact on season for both species. Analyses also highlighted considerable latency in models (> 49%) suggesting that additional aspects related to the dominant agriculture affect stork breeding success. Lowland Nepal’s agricultural landscapes provide important ecosystem services in providing habitats that support successful breeding of the focal stork species, one of which is globally vulnerable. Retaining even heavily-used wetlands in such human-dominated areas will benefit waterbird breeding.